1997
DOI: 10.1002/(sici)1097-4652(199708)172:2<240::aid-jcp11>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Moloney murine leukemia virus long terminal repeat activates monocyte chemotactic protein-1 protein expression and chemotactic activity

Abstract: Moloney murine leukemia virus (Mo-MuLV) is a thymotropic and leukemogenic retrovirus which causes T lymphomas. Recently, Mo-MuLV has been shown to trans-activate cellular genes. Monocyte chemoattractant protein-1 (MCP-1) is a chemokine which can promote the migration and diapedesis of monocytes and lymphocytes, as well as inducing metastasis of lymphomas. Here we demonstrate that introduction of Mo-MuLV or the MuLV LTR alone, transiently or stably, into Balb/c-3T3 cells or HeLa cells resulted in 9-11 fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…The level of activation of the MHC class I genes was consistently much lower than what we had observed with the Mo-MuLV LTR, however. No transactivation of other promoter-reporter vectors was observed, demonstrating that transactivation by the FeLV LTR has specificity in terms of the responsive genes, just as has been reported for murine retroviral LTRs (24,25,41). Similar patterns of gene activation were seen with NIH 3T3 cells.…”
Section: Fig 4 Transcriptional Activation Of Collagenase Promoter-rsupporting
confidence: 61%
See 1 more Smart Citation
“…The level of activation of the MHC class I genes was consistently much lower than what we had observed with the Mo-MuLV LTR, however. No transactivation of other promoter-reporter vectors was observed, demonstrating that transactivation by the FeLV LTR has specificity in terms of the responsive genes, just as has been reported for murine retroviral LTRs (24,25,41). Similar patterns of gene activation were seen with NIH 3T3 cells.…”
Section: Fig 4 Transcriptional Activation Of Collagenase Promoter-rsupporting
confidence: 61%
“…It has been proposed that the U3 region of the FeLV LTR plays a role in the disease pathogenesis similar to that of the MuLV LTR U3 region (30,32,48). Studies from our laboratory have shown that the U3 region of Mo-MuLV can transcriptionally upregulate the expression of certain cellular genes (24,25,41,73). We initially wished to determine if the U3 region from the FeLV-A virus has similar transactivation potential.…”
Section: Felv Ltrs Activate Collagenase Gene Expression Felv-amentioning
confidence: 99%
“…MCP-1 expression is transcriptionally regulated. A variety of factors, which include tumor necrosis factor-␣ (TNF) 1 (11), platelet-derived growth factor (PDGF-BB) (12), interferon-␥ (13,14), stress factors (15)(16)(17), and viral infection (18), induce MCP-1 transcription. In contrast, retinoic acid, glucocorticoids, and estrogen inhibit induced MCP-1 expression in certain cell lines (19 -22).…”
mentioning
confidence: 99%
“…atherosclerosis [32] and multiple sclerosis [33]. The expression of MCP-1 is regulated by cytokines including tumour necrosis factor (TNF) [34], platelet-derived growth factor (PDGF) [35], interferon-g (IFN-g) [36] and IL-1b [23,37], but stress factors and viral infections also cause MCP-1 expression [38,39]. Several regulatory promoter regions important for MCP-1 expression have been identified.…”
mentioning
confidence: 99%